Pembelajaran Kooperatif Berbasis Tutor Sebaya untuk Meningkatkan Hasil Belajar IPA Materi Pesawat Sederhana di SMPN 1 Kayangan - Siti Sujiati (Jurnal Paedagogy, 2020)
The research aims to describe the cooperative learning strategies of peer tutor types that can improve the learning outcomes of Science students grade VIII SMP Negeri I Kayangan. This research uses a qualitative approach and the type of research done is research into class action. This research was conducted at SMPN I Kayangan in Juli- September 2019 in 2 phases, namely pre action and stage of action. The action phase is implemented in 2 cycles and each cycle consists of 3 meetings. The results of this research can be concluded that the steps of Science learning that can improve student learning results are initiated by the presentation of the class by the teacher, the formation of groups heterogeneous, each group led by tutors Peers, teachers control when discussions take place, giving students time for class presentations, and ending with guiding students to conclude the material they are learning. Meanwhile, the increase of learning to learn students from cycle I test results and cycle test results II 65.39%.